BIOCHEMICAL, PURIFICATION, SEQUENCING AND ALIGNMENT STUDIES OF THE NOVEL POLYPHENOL OXIDASE ISOFORMS FROM MUSA ACUMINATA FRUIT PULP - N. Sajjad; S. M. S. Naqvi; M. J. Asad; N. I. Raja2 M. Pusztai-Carey; M. S. Ahmad1 (Journal of Animal and Plant Sciences, 2020)
Polyphenol oxidases (PPOs) are copper containing enzymes that play a significant role in the browning of fruits and vegetables by catalyzing hydroxylation and oxidation reactions. Currently, PPO gained significant interest of the researchers due to its potential applications in food, paper, pulp and, textile industries and also in pharmaceuticals. The present study was designed to purify and characterized PPO isoforms from fresh banana fruit pulp. The three novel active PPO isoforms (65 kDa, 45 kDa, 28 kDa) were detected by gel filtration chromatography and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The purified isoforms were further studied for the optimum pH (6.5), temperature (40°C), Michaelis constant (Km) and maximum reaction velocity (Vmax). The N-terminal microsequencing was performed on applied biosystem’s pulse liquid protein sequencer and was found to be 28 kDa (Alanine, proline, asparagine, serine, arginine) and 45 kDa (Alanine, proline, isoleucine, alanine, proline). Sequences were aligned by CLUSTALW and showed significant similarity with previously reported banana PPOs.
Keywords: PPO isoforms; gel filtration chromatography; N-terminal sequencing; multiple sequence alignment